Road adventure as a type of legal facts in the civil law of Ukraine - Vashchuk , Yaroslav (Actual problems of law (Aktual’ni problemi pravoznavstva), 2025)
The article examines the civil-legal dimension of traffic accidents (RTAs) and their consideration as torts giving rise to non-contractual obligations to compensate for damage. Despite the numerous normative legal acts defining RTAs, their analysis from the point of view of private law reveals peculiarities compared to administrative offenses. RTAs can be considered as complex legal facts - torts consisting of interrelated elements. In contrast to the administrative legislation, the presence of fault is not mandatory for the prosecution of the owner of the source of increased danger, which caused the RTA. An RTA can cause civil liability without the fault of the tortfeasor, if the damage was caused by the activity of the source of increased danger, such as the operation of a vehicle. The concept of responsibility for the risk is applied because the owner of the vehicle voluntarily assumes the risk. The analysis highlights the differences between RTAs as administrative offenses and torts: the presence of damage by third parties is important for civil liability, but is not always necessary for administrative prosecution under certain regulations. In addition, law enforcement practices may lead to incomplete statistics of the causes of RTA. While most RTA classifications focus on violation mechanisms, some scholars suggest classification by cause, including driver/pedestrian violations, force majeure, and vehicle maintenance issues — an approach worthy of attention as it can inform liability determinations. The perspective of autonomous vehicles causing RTAs is a new challenge that calls for new approaches to allocating responsibility between the driver, manufacturer and others based on the objective ability to prevent accidents. In summary, understanding the civil law nature of RTA as a tort is crucial for the proper regulation of compensation for damages in RTA, taking into account the specifics of liability for sources of increased danger under civil law.